Elementos de gestión para un Servicio de Urgencia de un hospital universitario - Tobar A., Eduardo; Retamal R., Andrea; Garrido C., Nicolás (Revista Hospital Clínico Universidad de Chile, 2014)
Emergency Departments (ED) are a key element of the health system, and for various reasons must face the phenomenon of overcrowding, which requires that the Director of Hospitals and Emergency teams to implement various improvements in clinical and administrative management of these units, all aimed at improving the quality of care with the patients and their families on the center of actions. All this in a service where the diagnostic accuracy is complex and service times play an important role. In this chapter we review some elements of management both in terms of people, as relevant critical processes in a shared vision for professionals in the field of health and management processes.